(untitled) (Environment & Health, 2023)
The aim of work was to study the features of the formation and removal of toxic chlorites at the treatment facilities of the Dnieper water pipeline in Kyiv, where chlorine dioxide is used in water treatment technology, and the influence of priority natural and technological factors on these processes. Materials and methods: The studies were carried out in 2021-2022. at the Dnieper waterworks in Kyiv, where chlorine dioxide is used instead of chlorine in water treatment technology. We have analyzed data from water studies for the content of dioxide and chlorites, carried out at treatment facilities by the laboratory of the Dnieper water pipeline in order to establish the features of the formation and efficiency of chlorite removal in water treatment technology. Also, selective studies of chlorine dioxide and chlorites in the water supply were carried out by titrimetric and photometric methods, the results of which coincide with the data obtained on the water supply using the ion chromatography method. Main results: A positive hygienic assessment of the modern new technology for the preparation of drinking water from surface sources using chlorine dioxide instead of chlorine gas is given. It is shown that with high purifying and disinfecting effects of water treatment with chlorine dioxide, its by-products, in particular, toxic chlorites, are constantly formed in it, the levels of which are directly dependent on the doses of chlorine dioxide used, which vary according to the seasons of the year. In general, the primary dose of chlorine dioxide and chlorites in the water after the clean water tank (CWT) entering the water supply networks is reduced by 89,3-92,0% for chlorine dioxide, and by 76,2-85,6% for chlorites. At the same time, the concentration of chlorine dioxide in disinfected drinking water is always within the normal range - not less than 0,1 mg/dm3, and chlorites - most often exceeds the national hygienic standard (0,2 mg/dm3), but does not exceed the standard recommended by the WHO ( 0,7 mg/dm3). The highest concentrations of chlorites are formed in water in summer (on average 0,35 mg/dm3) in accordance with the increased doses of chlorine dioxide during this period (on average 2,51 mg/dm3), and the lowest in winter (on average 0,17 mg/dm3). Conclusions: The studies carried out at the Dnieper water pipeline, where chlorine dioxide was introduced into the traditional water treatment technology, made it possible to establish the following. The process of treating natural water with chlorine dioxide is accompanied by the formation of its by-products in water, mainly toxic chlorites, the levels of which depend on the doses of chlorine dioxide used and are the lowest in winter and summer. After coagulation treatment of the source water with aluminum sulfate and ferric chloride (ratio 10:4-5), settling and filtration, the levels of chlorites in drinking water (CWT) decrease intensively, but do not always reach regulatory values. In the summer period, the maximum levels of chlorites in drinking water with RCHV can be higher than the national hygienic standard (0,2 mg/dm3) and range up to 0,7 mg/dm3, which corresponds to the WHO recommended standard for this substance in drinking water. The issue of revising the national standard for chlorites in water from 0,2 mg/dm3 to 0,7 mg/dm3 after appropriate scientific justification is being raised.